Study on the Evaluation of Carbon Emission Efficiency of Land Use in Chengdu-Chongqing City Cluster - Li, Jiandong; Yin, Chaoyin; Qiu, Huiyu (International Journal of Global Economics and Management, 2025)
Land is the carrier of human survival, and exploring land use carbon emissions and its efficiency is extremely important for implement low-carbon land use and local future development planning. Based on the data of Chengdu-Chongqing City Cluster, this paper explores the changes of land use carbon emission and its efficiency of 16 cities in the Chengdu-Chongqing City Cluster from 2014 to 2022 by using relevant models and software, and analyses the results. The results show that (1) in terms of carbon sinks, since the Chengdu-Chongqing City Cluster is in the southwestern part of the country and has rich vegetation cover, while Chongqing has the largest area under its jurisdiction, it has the largest amount of carbon sink absorption, followed by Ya'an and Mianyang. (2) As for carbon sources, it is related to the degree of regional development, and since Chengdu and Chongqing are the best developed, their carbon emissions are the largest. (3) In terms of carbon emissions, based on the data of carbon sinks and sources, it is concluded that Chongqing and Chengdu have the largest carbon emissions. (4) In terms of carbon emission efficiency, Chengdu's carbon emission efficiency has always been growing steadily, while the rest of the cities have both increases and decreases.